2016
DOI: 10.1055/s-0036-1584325
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Manifestations of Mycoplasma pneumoniae Infection in Hospitalized Children and Their Long-Term Follow-Up

Abstract: Objective In this retrospective study, we aimed to assess frequency, types, and long-term outcome of neurological disease during acute Mycoplasma pneumoniae (M. pneumoniae) infection in pediatric patients. Materials and Methods Medical records of patients hospitalized with acute M. pneumoniae infection were reviewed. Possible risk factors were analyzed by uni- and multivariate regression. Patients with neurological symptoms were followed up by expanded disability status score (EDSS) and the cognitive problems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 24 publications
4
19
0
2
Order By: Relevance
“…Involvement can occur in the brain, spinal cord, meninges, and peripheral nerves. The primary brain manifestation is encephalitis, which occurs more commonly in children than in adults and may not have a respiratory component to the illness (180,(238)(239)(240)(241)(242)(243). M. pneumoniae may be responsible for as many as 13% of encephalitis cases (244).…”
Section: Extrapulmonary Manifestationsmentioning
confidence: 99%
“…Involvement can occur in the brain, spinal cord, meninges, and peripheral nerves. The primary brain manifestation is encephalitis, which occurs more commonly in children than in adults and may not have a respiratory component to the illness (180,(238)(239)(240)(241)(242)(243). M. pneumoniae may be responsible for as many as 13% of encephalitis cases (244).…”
Section: Extrapulmonary Manifestationsmentioning
confidence: 99%
“…Poor correlations between serology and PCR assessments for MP infections in patients with neurological manifestations make the diagnosis difficult, especially because it prevents identification of the convalescent phase [ 5 ]. A long-term follow-up study of children with MP infections reported cases of significant neurological disability [ 51 ].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Although M. pneumoniae pneumonia (MPP) is usually considered a self-limited disease, it may trigger pulmonary complications that may progress into refractory M. pneumoniae pneumonia (RMPP), severe M. pneumoniae pneumonia (SMPP), and even lethal pneumonia [9,10]. Meanwhile, some may present concurrent infection and multiple-organ infection, which results in poor prognosis [11,12]. erefore, M. pneumoniae infection is a heavy burden to the pediatric practice worldwide.…”
Section: Introductionmentioning
confidence: 99%